OBSERVATIONS CONCERNING THE PSYCHOANALYTIC PHILOSOPHY OF CULTURE - PETROSYAN, SILVA (Bulletin of Yerevan University E: Philosophy, Psychology, 2020)
In the article, an attempt is made to consider the psychoanalytic philosophy of culture in the context of the history of the philosophy of the XIX-XX centuries. Psychoanalysis is one of the most influential areas of psychology of the last century, in which philosophical generalizations about a person and culture are clearly traced. The article analyzes the teachings of Sigmund Freud and Carl Gustav Jung on culture, the key concepts of these theories, and also presents some works, in particular, the work concerning Leonardo da Vinci. The article shows that psychoanalysis has changed the approach to a human as a cultural being, linking the psyche of a modern human with the whole history of mankind. The article also discusses the influence of the psychoanalytic concept of culture on the anthropological and philosophical thought of the last century, in particular, philosophical anthropology, Freudo-Marxism, etc. Some parallels with Armenian reality are also drawn.
Keywords: Freud, Jung, sublimation, Leonardo da Vinci, neurotic, pre-human, archetype, Anti-Oedipus, Freudo-Marxism, postmodernism